Constraining Factors of Research among faculty members at Hormozgan University of Medical Sciences - Nejatizadeh, Azim (Electron Physician, 2016)
INTRODUCTION: In recent decades, the major criteria for development in countries were defined mostly by research position. The first step in organizing the research subject in societies is gaining a correct perception of abilities, available facilities, and finding the strengths and weaknesses of research programs. This research was conducted to determine the constraining factors of research among faculty members. METHODS: In this cross-sectional study in 2013, the population was Hormozgan Medical Science faculty members, and samples were selected based on the Morgan table (138 individuals). A researcher-made questionnaire after determining validity and confirming reliability was distributed among them. The data were analyzed by SPSS using descriptive and inferential statistics, such as Pearson’s product-moment correlation. RESULTS: Among organizational factors, lack of data presentation to researchers from organization sections with 81.2% was the most effective factor. The lack of facilitating national and international research exchange with 80.5% and the lack of research workshops based on needs with 77.9% were the next ones. Among the personal constraining factors, 64% of the faculty declared that having inadequate time for research due to the educational activities was the main factor. CONCLUSIONS: According to the faculty’s comments, research activities encounter different constraining factors. It can be said that, by promoting a data registration system, collaborating on contract agreements and improving national and international research exchange, empowering members’ research (need-based workshops), and decreasing the faculty’s clinical and educational activities can overcome these constraints.